Analisis SWOT dalam Penelitian Manajemen Dakwah - Tampubolon, Ichwansyah (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2020)
Qualitative research on the reality of da'wa management can use one of models of analysis named SWOT analysis. SWOT analysis aims not only to identify both of internal and external factors that can support or inhibit the course of da'wa activities but also to know and measure the strengths, weaknesses, opportunities, and threats faced by the da'wa activities. These preliminary data of da`wa activities are most important to stakeholders who want to provide a scientific recommendation for planning the goals, developments and targets of Â da`wa or to applicate da'wa strategies in order to make a positive change of socio-religious life of ummah for the better.